A twenty-first century framework for Australian metropolitan governance. Issue 2 (3rd April 2020) - Nicholls, Luke; Spiller, Marcus
ABSTRACT: Australia has a weakness in metropolitan-level governance for our major cities. With the challenges facing Australian cities and communities in the twenty-first century, re-engagement with how to improve the governance of cities will be an important factor in ensuring their liveability, sustainability and competitiveness. This paper draws on the literature, and our practitioner experience, to derive a framework and key pillars of reform to guide metropolitan governance development. This framework considers the unique characteristics of Australia's metropolitan governance, which is dominated by State and Territory governments.